2022
DOI: 10.3390/bios12060397
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Graphene-Based Wearable Epidermal Ion-Selective Sensors for Noninvasive Multiplexed Sweat Analysis

Abstract: Wearable sweat sensors are a rapidly rising research area owing to their convenience for personal healthcare and disease diagnosis in a real-time and noninvasive manner. However, the fast and scalable fabrication of flexible electrodes remains a major challenge. Here, we develop a wearable epidermal sensor for multiplexed sweat analysis based on the laser-induced graphene (LIG) technique. This simple and mask-free technique allows the direct manufacturing of graphene electrode patterns on commercial polyimide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Epidermal wearable biosensors have been manufactured on a variety of substrates, such as textiles [ 114 , 123 , 124 , 152 , 155 , 156 ], tattoos [ 40 , 80 , 81 , 93 , 157 ], and patches and bandages [ 149 , 151 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ].…”
Section: Sweat Sensing Platformmentioning
confidence: 99%
“…Epidermal wearable biosensors have been manufactured on a variety of substrates, such as textiles [ 114 , 123 , 124 , 152 , 155 , 156 ], tattoos [ 40 , 80 , 81 , 93 , 157 ], and patches and bandages [ 149 , 151 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ].…”
Section: Sweat Sensing Platformmentioning
confidence: 99%
“…The LIG-based sensors showed good performance, with sensitivities of 51.5 mV/decade (pH), 45.4 mV/decade (Na + ), and 43.3 mV/decade (K + ), and the sensing performance was well-maintained under bent states. Good reproducibility, stability, and selectivity were also observed [ 109 ].…”
Section: Wearable Biosensors Based On 2d Materialsmentioning
confidence: 99%
“…It has led to the generation of extensive attention towards the development of sweat-sensing devices (SSDs) as a diagnostic biofluid. A growing number of research studies that have been reported on analyzing various sweat biomarkers for use in a broad range of clinical diagnostic purposes, including health concerns, nutritional imbalance, drug abuse, and many more [ 1 , 2 , 3 , 4 ], have seen a ten-fold rise in this field, as shown in Figure 1 . However, there are still gaps in the structured content on related SSD applications based on the current existing review articles, such as insufficient information about a few sweat biomarkers, especially hormones, drugs, nicotine, and vitamin C, and inadequate detailed explanation of the respective application concepts related to these biomarkers and a lack of a fundamental response mechanism of chemical sensors that enable users to understand the process of the target analyte’s detection for various sweat compositions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%